Vibrações mecânicas e seus efeitos no bem-estar de tilápia do Nilo (Oreochromis niloticus) durante o transporte - Rebouças, Perila Maciel (2019)
Oscillatory movements present in live fish transportation can compromise the animals’ physiological stability. Therefore, this research aimed to evaluate, in a real production environment, the effects of the transport vibrations and mechanical shocks on Nile tilapia stress and performance. The vibrations were obtained through sensors previously installed in a transport box fixed to the truck. Five purpose-built datalogger sensors recorded g-force, truck speed, water temperature, and geographical location, as well as mechanical shock and vibration levels through all the way. The experiment was conducted by an integrated fish farming company in the state of Ceará/Brazil, monitoring 5 different live fish batches. The vehicle used for the transport was an open type truck, with capacity for five fiberglass boxes with a maximum volume of 2400 L, density of 236 kg / m3. The transport period lasted on average three hours for each treatment and the fish had their parameters (weight difference, weight-length relationship and condition factor (Kn), physical injuries, metabolic, ionic and hematological responses) compared to control groups (without vibration). The most intense shocks occurred when the truck was between 60 and 80 km / h, resulting in vibrations of 1.151 m / s2 in the transport box, as well as in the water of 0.489 m / s2. Higher vibration levels occurred on the asphalt road, with an average value of 1.13 m / s2, while on the dirt road they averaged 0.57 m / s2. Tilapia presented secondary responses to stress on blood level with significant changes in magnesium ions, glycemia, hematocrit, and hemoglobin, as well as live fish load losses of 0.47% and 0.80% kg, respectively, in the truck and the transport box after the transportation. Physical injuries at 34% severity and 21% moderate showed an uncomfortable environmental condition to organisms, although there was no significant difference in the weight-length relationship and post-transport condition factor. Thus, it is concluded that vibrations and mechanical shocks may act as a potential stressor in the transport of these fish over short distances, but do not compromise the tilapia's productive performance, if they occur under conditions similar to those performed in this research.